Alltagspraxis zwischen Regularisierung und Wohnungsmarkt am Beispiel der Villa 31 in Buenos Aires - Naue, Sophie (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2017)
The present work "Everyday practice between regulation and informal housing market" deals with the Villa 31, an informal settlement in the centre of Buenos Aires. The Villa 31 was established in the 1930s, today it is the home of more than 27.000 people, many of whom continue to live under precarious living conditions without legalized forms of possession. Initial point of the research project is the law No 3.343 which was discussed controversially but finally enacted in December 2009. The law establishes the preservation and reassessment (the so called urbanization) of the Villa 31. Based on the research drawn from this specific place, the dissertation concentrates on two present developments: on the one hand the process of reassessment of the Villa 31 is examined, which has been initiated and established by the city administration. On the other hand the analysis focuses on the development of a parallel functioning informal housing market within the settlement. The explicit intention is the critical analysis of topics that are underrepresented in the scientific sphere (from the inhabitants´ point of view). The knowledge of the local conditions generates an empirical basis and contributes to a better understanding of the specific dynamics of the settlement Villa 31. The first part of the dissertation concentrates on the process of urbanization, more specifically on the reassessment of the Villa 31. In this context, the impact of publicly controlled urbanization and its effects on the settlement and its people is examined. The research starts from two different perspectives: the first analyses and questions the procedures and intentions of the formal planning of the city administration in the context of the state- run and controlled urbanization of the Villa 31. The second considers the process from the urban practice and everyday perspective of the inhabitants of the Villa. A comprehensive snapshot of the present process of urbanization emerges, demonstrating the underlying living realities in this urban place as well as different perspectives of the inhabitants, otherwise beyond general perception. In the second part of the dissertation the focus of research lies on the development and establishment of an independent housing market within the Villa 31. In the centre of interest are the practices of the appropriation of housing (habitat) and their transformation by the rules of the informal housing market. In this context the question is examined how the functioning of the housing market and the implementation of urbanization are related. In interviews with local protagonists of the housing market the basic conditions, the change of property and renting conditions, the transformation of housing on offer as well as the ruling economic factors and guarantees are examined. A comprehensive elaboration of the way the housing market functions and the mechanisms of negotiation emerges. The knowledge generated in the analysis provides an empiric basis for future possibilities in working with the housing market of the Villa 31.

Die vorliegende Arbeit "Alltagspraxis zwischen Regularisierung und Wohnungsmarkt" beschäftigt sich mit der Villa 31, einer informell gewachsenen Siedlung im Stadtzentrum von Buenos Aires. Die bereits in den 1930er Jahren entstandene Villa ist heute Lebensraum von mehr als 27.000 Menschen, die zum Teil noch immer unter prekären Wohnbedingungen und in ungeklärten Besitzverhältnissen leben. Den Ausgangspunkt des Forschungsvorhabens bildet in diesem Zusammenhang das lange Zeit kontrovers diskutierte, letztlich jedoch im Dezember 2009 erlassene Gesetz No 3.343 welches den Erhalt und die Aufwertung (die sog. Urbanisierung) der Villa 31 rechtlich verankert. Ausgehend von dem spezifischen Ort konzentriert sich die Arbeit auf zwei gegenwärtige Entwicklungen, zum einen wird die Etablierung des städtisch initiierten Aufwertungsprozesses der Villa 31 untersucht, zum anderen fokussiert sich die Analyse auf die Entstehung eines parallel funktionierenden Wohnungsmarktes innerhalb der Siedlung. Im Vordergrund steht dabei die kritische Analyse der bislang wissenschaftlich nicht erforschten Themenfelder aus der Perspektive der Bewohner_Innen. Der erste Teil der Dissertation konzentriert sich auf den Urbanisierungs- bzw. den Aufwertungsprozess der Villa 31. Die Untersuchung erfolgt dabei ausgehend von zwei verschiedenen Blickrichtungen: auf der einen Seite werden die Vorgehensweisen und Absichten der formellen Planung der Stadtverwaltung dargelegt und hinterfragt, zum anderen wird der Prozess ausgehend von der urbanen Praxis und Alltagsperspektive der Bewohner_Innen betrachtet. In diesem Zusammenhang wird der Fragestellung nachgegangen, welche Auswirkung die öffentlich gelenkte Urbanisierung auf den Siedlungsraum und die Menschen vor Ort hat. Es entsteht eine umfassende Momentaufnahme des laufenden Urbanisierungsprozesses, die sowohl die zugrundeliegenden stadträumlichen Lebensrealitäten aufzeigt als auch verschiedene Perspektiven der Bewohner_Innen darstellt, die sonst meist außerhalb der allgemeinen Wahrnehmung liegen. Im zweiten Teil der Arbeit liegt der Forschungsfokus auf der Etablierung und Entwicklung des eigenständigen Wohnungsmarktes innerhalb der Villa 31. Die Praktiken der Wohnraumaneignung und deren Veränderung durch die Prinzipien des Wohnungsmarktes werden dabei in den Mittelpunkt gestellt. In diesem Zusammenhang wird der Fragestellung nachgegangen, in welchem Verhältnis die Funktionsweise des Wohnungsmarktes und die Umsetzung der Urbanisierung stehen. Ausgehend von den lokalen Akteur_Innen auf dem Wohnungsmarkt werden anhand von Interviews die Veränderung der Eigentums- und Mietverhältnisse, die Transformation des Wohnraumangebotes sowie die vorherrschenden ökonomischen Rahmenbedingungen und Sicherheiten untersucht. Es entsteht ein umfassendes Bild der Aushandlungsmechanismen und Funktionsweise des Wohnungsmarktes. Durch die Kenntnis der lokalen Bedingungen und deren Analyse wird eine empirische Grundlage generiert, die zum besseren Verständnis der spezifischen Siedlungsdynamik beiträgt.
Everyday practice between regulation and informal housing market
Keywords: Wohnungsmarkt; 710 Städtebau, Raumplanung, Landschaftsgestaltung